Pelatihan Pengembangan Media Pembelajaran Interaktif Berbasis Audio Visual Bagi Mahasiswa PGSD Universitas Lampung - Sheren Dwi Oktaria; Destiani; Roy Kembar Habibi; nindy profitha; Siti Nuraini; Jody Setya Hermawan; Hariyanto (Jurusan Ilmu Pendidikan - Universitas Lampung, 2022)
The use of audio-visual media in learning will increase students' motivation and learning outcomes. Students from the PGSD Study Program, University of Lampung as prospective educators are required to be able to innovate creatively by utilizing technological advances for learning media. One of them is using camtasia studio media. So that students are able to use Camtasia perangkat lunak, training in the development of interactive media based on Camtasia audio-visual is needed. After attending this training, PGSD students understand and use the features of Camtasia Studio. So that students are able to modify the learning media into interactive audio-visual learning media.